Moderate and extended neonatal resuscitations occur in one in 10 births and require specialist cover 24 hours a day. (3rd March 2015) - Try, Alyssa; Karam, Oliver; Delcò, Cristina; Kraemer, Karin; Boulvain, Michel; Pfister, Riccardo E.
Abstract Aim Neonatal resuscitation requires minimal equipment, but the immediate availability of expert staff accounts for the largest proportion of the costs. Despite this, staff requirements and timetables are currently planned without comprehensive epidemiologic data. The aim of this study was to evaluate the staffing required for neonatal resuscitations in the delivery room. Methods We measured attendance for each specific role in a tertiary university‐affiliated hospital and for four possible intervention levels: preparation time, basic paediatric care, moderate resuscitation and extended resuscitation. Results Between 2005 and 2012, resuscitation staff attended 11 561 of the 32 799 births: 27.2% for preparation time, 17.7% for basic paediatric care, 6.4% for moderate resuscitation and 3.5% for extended resuscitation. Moderate and extended resuscitations occurred in roughly 10% of births and evenly during 24‐h periods. Basic paediatric care levels were higher during weekday mornings, and extended resuscitations were uniformly distributed. However, there was a drop in all types of interventions around 7 a.m. to 8 a.m., when staff were changing shifts. Conclusion Moderate and extended resuscitations occurred evenly over 24 h in roughly 10% of births, stressing the importance of having a highly competent neonatal team constantly available. All activities associated with resuscitation were lower during morning shift changes.